2023
DOI: 10.3390/molecules28166148
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Composition of Carlina acaulis L. Extract and Cytotoxic Potential against Colorectal Adenocarcinoma and Cervical Cancer Cells

Ireneusz Sowa,
Jarosław Mołdoch,
Roman Paduch
et al.

Abstract: Carlina acaulis is highly valued in the traditional medicine of many European countries for its diuretic, cholagogue, anthelmintic, laxative, and emetic properties. Moreover, practitioners of natural medicine indicate that it has anti-cancer potential. However, its phytochemistry is still little known. In the present study, the polyphenolic composition of the plant was investigated using ultra-high-performance liquid chromatography coupled with a high-resolution/quadrupole time-of-flight mass spectrometer (UHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…[ 20 ] In other studies, the ethyl acetate fraction of Carlina acaulis L. also tended to show the strongest cytotoxic effect against human colorectal adenocarcinoma cancer cells (HT29) and human cervical cancer cells (HeLa) compared to other organic solvent fractions. [ 10 ] This indicates that ethyl acetate as a semipolar solvent dissolves more semipolar active substances (e.g., flavonoids, triterpenoids, and alkaloids), which are proven to have anticancer effects. [ 24 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] In other studies, the ethyl acetate fraction of Carlina acaulis L. also tended to show the strongest cytotoxic effect against human colorectal adenocarcinoma cancer cells (HT29) and human cervical cancer cells (HeLa) compared to other organic solvent fractions. [ 10 ] This indicates that ethyl acetate as a semipolar solvent dissolves more semipolar active substances (e.g., flavonoids, triterpenoids, and alkaloids), which are proven to have anticancer effects. [ 24 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Furthermore, the cytotoxic potential of the Carlina acaulis L. plant in the ethyl acetate fraction (the most abundant polyphenolic compound and the strongest antioxidant potential) against human colorectal adenocarcinoma (HT29) and human cervical cancer (HeLa) cells shows the most promising anticancer activity. [ 10 ] Thus, polyphenols contained in the phenolic and flavonoid compound groups have a relationship with antioxidant and anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence has shown that the species exhibits antioxidant, antibacterial, antifungal, and anti-ulcer properties [ 7 , 8 , 9 ]. Additionally, it has been found to be cytotoxic against a few types of cancer cell lines [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%